An Investigation of the Sports Awareness of Employees in Sports Management According to Several Variables - Murat Kalfa; Şahin Bayzan (Pamukkale University, 2023)
This study aims to raise the awareness of public employees in sports administration through various types of training to measure the awareness of public employees working in sports administration regarding sports, as well as to reveal the problems facing sports in Turkey from the perspective of those working in sports administration. The research was carried out with a mixed methods convergent parallel design of the questionnaire variant. The study population consists of employees working in the central and provincial organizations of the Ministry of Youth and Sports, and the sample consists of 581 people working under different titles determined by the convenience sampling method. SPSS 24 and NVIVO 10 package programs were used for data analysis. The findings show that the awareness of those working in sports management is higher among men than women, that for those who have just started their professional life, it is higher than for others, and that those who have been working in sports management for a long time increase their awareness over time. The most critical problems of Turkish sports are stated as lack of infrastructure, lack of merit, lack of sustainable sports policy, discontinuity of studies, insufficient sports awareness education, and insufficient awareness of directing children to sports at an early age.